Effects Of Oil Palm Frond Methanolic Extract On Blood Pressure, Antioxidant Status And Selected Organs Of Nitric Oxide-Deficient Rats - Md Jaffri, Juliana (2009)
Hypertension is a modifiable risk factor for cardiovascular disease (CVD). Diet intervention by increasing the intake of fruits and vegetables proved to be beneficial by reducing blood pressure (BP) and lowering the risk of CVD. Apart from micronutrients, the phytochemical content of fruits and vegetables has been associated with the BP lowering effect. Hypertension is commonly associated with a reduced vascular nitric oxide (NO) due to excessive degradation by reactive oxygen species (ROS). In addition, NO is also important in maintaining organ functions and perfusion. In this study normal and NO deficient rats were used to evaluate the BP lowering effect and antioxidative property of oil palm frond methanolic extract (OPFME). The protective effect of OPFME in the liver, heart, kidney and brain of these rats were assessed and any toxicity effect was also investigated. Two major groups of rats (normal and NO deficient groups) were further divided into three sub-groups; the first subgroup received the vehicle used to dilute OPFME; the second subgroup received OPFME and the third subgroup received captopril. NO deficiency was induced by administration of N-ω-nitro-L-arginine methyl ester (L-NAME). Erythrocyte/organ superoxide dismutase (SOD), catalase and glutahione peroxidase (GPx) activities, and plasma/organ malondialdehyde (MDA) concentration were measured. Livers, hearts, kidneys and brains were removed at the end of the study. Histological appearances of these organs were examined. Kidneys were functionally evaluated by measurement of plasma creatinine and urea concentrations, whereas liver function was tested by measuring plasma alanine aminotransferase (ALT), aspartate aminotransfersa (AST), and alkaline phosphatase (ALP). OPFME significantly attenuated BP increases in NO deficient rats comparable to captopril, and temporarily improved antioxidant status. In the liver OPFME partially protected hepatocytes from extensive injury due to NO deficiency. OPFME also partially prevented coronary arterioles from thickening, but failed to inhibit structural changes in the left ventricle. The glomeruli of OPFME treated NO deficient rats were not improved. Slight renal tubular dilation observed in normal rats treated with OPFME is a matter of concern and should be further investigated. OPFME showed remarkable hippocampal neuroprotection and this correlated well with its antioxidative property in the brain. There was no neurotoxic effect of OPFME observed. On the contrary, neurogenesis was displayed as an increase in the number of viable granule cells of the dentate gyrus (DG) of normal rats treated with OPFME. In conclusion, OPFME was effective in suppressing BP increment during NO deficiency. The extract was also partially hepatoprotective and significantly neuroprotective. However, OPFME may induce nephrotoxicity and should be investigated further for clarification.